Marketing Strategies That Impact Patient Loyalty in Hospitals: An Empirical Literature Perspective: Marketing Strategies - Irawan, Muhammad Henrie; Khrisnamurti, Valencia Ursula; Iftiah, Nia (Open Access Health Scientific Journal, 2025)
Background: In an era of increasingly tight healthcare competition, patient loyalty is an important indicator of hospital success. This loyalty is not only influenced by the quality of medical services alone, but also by the effectiveness of the communication and marketing strategies implemented. Hospital marketing strategies that are able to build long-term relationships with patients are now the focus of study, especially in the context of how these strategies can increase patient trust and retention. Therefore, it is important to identify marketing strategies that have been empirically proven to have an impact on patient loyalty.Methods: This study uses a systematic literature review approach, which examines and evaluates five selected scientific papers from various hospital contexts in Indonesia and Japan. The literature review involves qualitative and quantitative studies to gain a comprehensive understanding of effective marketing strategies. The selection process of articles is based on their relevance, credibility, and contribution to the topic of patient loyalty in healthcare marketing.Results: The results of the analysis show that the two main strategies that are dominant and significant in increasing patient loyalty are Integrated Marketing Communication (IMC) and relationship marketing.Conclusion: This study confirms that patient loyalty is not only formed by the quality of medical services, but also by integrated, adaptive, and long-term-oriented communication and marketing strategies. These findings provide an important contribution in formulating more strategic health service marketing policies that focus on sustainable patient relationships, so that they can be a practical reference for hospital managers in increasing institutional competitiveness.